Explaining the Livability of Isfahan City Based on Life City Discourse - Seyed Ali Hashemianfar; Ahmad Mehrshad; Mohammad Heydari; Nariman Mohammadi (Strategic Research on Social Problems)
IntroductionUrbanization, a defining characteristic of the 20th century, has been linked to enhancements in citizens' welfare and well-being, as well as a reduction in societal problems. This evolution has been shaped by philosophical attitudes and various plans and projects over time. The city serves as a dynamic environment where individuals interact as influenced by their relationships and the city’s physical, historical, social, and cultural elements. Consequently, the city—both as context and space—plays a significant role in shaping citizens' lifestyles and quality of life impacted by urban policymaking, planning, and management discourse. Given the broad and diverse scope of urban management, establishment of a coordinated framework for urban activities is both essential and inevitable. Addressing urban issues in a coherent and integrated manner necessitates a coordinated effort akin to an orchestra performed collectively by city and urban management under a shared discursive framework. In this context, Isfahan's urban management has adopted the cultural slogan “My Isfahan, the City of Life”, aiming to positively shape this discourse. Achieving this vision, however, requires specific mechanisms and conditions at various levels. This study employed a mixed-methods approach and sought to address the following questions in its initial phase through qualitative research: (1) What is the current state of Isfahan and its municipality? (2) What meaning and conceptual framework can be defined for the “City of Life” in relation to the current situation? In the second phase, the study used quantitative research to evaluate the “City of Life” framework based on the qualitative findings and quantified the relationships among the concepts within the conceptual network of this discourse. Ultimately, by synthesizing results from both research phases through meta-inference, the study aimed to provide a comprehensive understanding of how to operationalize this discourse.  Materials & MethodsThis research was conducted within the pragmatism paradigm, employing a mixed-methods approach. A sequential design with an exploratory strategy was implemented. The first phase utilized qualitative content analysis, specifically employing causal layered analysis as the research strategy. The second phase adopted a survey methodology. In the qualitative phase, the population included documents, sources, and texts related to Isfahan, while the research participants consisted of urban experts and managers. For the quantitative phase, the population comprised citizens aged 25 years and younger. All relevant sources and texts concerning urban policymaking, planning, and management were reviewed in the qualitative phase with 12 urban experts and managers selected through purposive sampling. In the quantitative phase, a sample size of 600 individuals was estimated, utilizing multi-stage cluster sampling. Data collection in the qualitative phase involved note-taking and interviews, while a researcher-developed questionnaire was employed in the quantitative phase. Data analysis in the qualitative phase was conducted using a coding technique based on the four layers of causal layered analysis. Descriptive and inferential statistical methods were applied for data analysis in the quantitative phase. To validate the qualitative data and findings, member checks and external audits were performed. In the quantitative phase, assessments of internal and external validity were conducted. Additionally, convergent validity was evaluated using Average Variance Extracted (AVE) and discriminant validity was assessed through Cross Loadings, Fornell and Larcker criteria, and the Heterotrait-Monotrait Ratio. The reliability of the questionnaire was measured using Cronbach’s alpha coefficient. Discussion of Results & ConclusionThe findings from the qualitative phase revealed that Isfahan faced significant challenges across 4 hierarchical and causal layers: the litany (low livability), social causes (systemic divergence and social discontinuity), discourse/worldview (discourse disorder), and myth/metaphor (untrustworthy municipality, a negligent city, and citizens viewed as broken tiles). These layers were interconnected; metaphors served as the foundational basis for the litany level of low livability, while the discourse and systemic causes mediated this relationship. Essentially, the influence of metaphorical and mythical structures on low livability was channeled through discursive frameworks and systemic factors. In the current context, the metaphor and myth layer had contributed to a disorderly discourse at the worldview and discourse levels. Urban negligence (from the metaphor and myth layer) had a direct positive impact on this discourse disorder. Consequently, urban negligence shaped and perpetuated discursive chaos. A disorganized metaphorical and mythical structure had often led to discursive instability. This disorder characterized by a lack of coherent frameworks had resulted in systemic divergence within urban institutions, social fragmentation among citizens, and a deficit in effective engagement between urban institutions and the community. The quantitative phase corroborated these qualitative findings. Citizens' assessments reflected low urban livability, moderate systemic divergence, social discontinuity, discourse disorder, low trust in the municipality, a relatively negligent city, and a somewhat positive sense of belonging to the city. Moreover, the quantitative results demonstrated that the variables of a negligent city, discourse disorder, and systemic divergence had significantly affected urban livability.